Performance of inflation targeting based on constant interest rate projections - Seppo Honkapohja; Kaushik Mitra (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Monetary policy is sometimes formulated in terms of a target level of inflation, a fixed time horizon and a constant interest rate that is anticipated to achieve the target at the specified horizon. These requirements lead to constant interest rate (CIR)instrument rules. Using the standard New Keynesian model, it is shown that some forms of CIR policy lead to both indeterminacy of equilibria and instability under adaptive learning. However, some other forms of CIR policy perform better. We also examine the properties of the different policy rules in the presence of inertial demand and price behaviour.
urn:nbn:de:hebis:30-10441
Keywords: E52; E61; E32; 330; Indeterminacy; instability under learning; inflation targeting; inertia in demand; inflation inertia; Inflation Targeting; Zins